2018
DOI: 10.2217/cns-2018-0006
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of D,L-methadone in the treatment of glioblastoma in vitro

Abstract: Aim:Recently, D,L-methadone has been put forward as adjuvant treatment in glioblastoma (GBM).Methods:We analyzed the μ-opioid receptor expression in a set of GBM cell lines and investigated the efficacy of D,L-methadone alone and in combination with temozolomide (TMZ).Results & conclusion:Expression of the μ-opioid receptor was similar in the tested cell lines. High concentrations of D,L-methadone induced apoptosis in all cell lines and showed treatment interaction with TMZ. However, in lower dosages, reflecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 46 publications
3
19
0
Order By: Relevance
“…Due to these shortcomings, we also tested the clinically more relevant drug TMZ in combination with MET. One study has already reported no effect of MET on TMZ-induced cytotoxicity in various GBM cell lines [15]. Similar observations were made in another study with GBM cells and MET applied together with TMZ or irradiation (4 Gy) [16].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Due to these shortcomings, we also tested the clinically more relevant drug TMZ in combination with MET. One study has already reported no effect of MET on TMZ-induced cytotoxicity in various GBM cell lines [15]. Similar observations were made in another study with GBM cells and MET applied together with TMZ or irradiation (4 Gy) [16].…”
Section: Discussionsupporting
confidence: 75%
“…It has previously been shown that the MOR is expressed in GBM cell lines and primary cells [9,15]. Here, we demonstrate expression of MOR in commonly used GBM cell lines (U87, U251, U373) and primary GBM cells isolated from a patient biopsy by Western blotting (Fig.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Conclusions in line with this were drawn from studies using a panel of glioblastoma cell lines expressing the µ-opioid receptor. The authors found no interaction of MTD with TMZ [ 24 ]. Similar observations were made in an independent study with glioblastoma cells and MTD administered together with TMZ or IR (4 Gy) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The postulated ability of methadone to enhance cancer therapy [ 16 , 17 , 18 ] has received considerable attention in recent years, but remains highly controversial. Preclinical evidence for a tumoricidal methadone effect has been obtained in vitro and in mouse models for various tumor identities, such as leukemia [ 17 , 18 , 78 , 79 , 80 ], glioblastoma [ 16 , 81 , 82 ], neuroblastoma [ 83 ], and carcinoma cells [ 13 , 14 , 83 , 84 , 85 , 86 ]. These studies are summarized in Table 3 .…”
Section: Evidence For a Tumoricidal Activity Of Methadonementioning
confidence: 99%